Unforgotten [large type] - Gray, Shelley Shepard (Thorndike Press large print Christian fiction series., 2024)
"Even though Bethanne Hostetler has found some peace seven years after an attempted assault and the accidental death of Peter Miller, she is still haunted by the memory. When her cousin, Candace, reveals that she has a stalker, all of Bethanne's old fears come rushing back. Jay Byler had once been Peter's best friend, and the fact that he did not protect Bethanne that fateful night has haunted him ever since. As Candace's stalker becomes bolder, Officer Ryan Mulany becomes her escort to various events. And when everyone's worst fears are realized, all four must work together to prevent another tragedy before time runs out and another innocent person is hurt."--